Effects of a high-fat, high-carbohydrate diet on the retina of young and old rats - S. V. Logvinov; L. R. Mustafina; B. K. Kurbatov; N. V. Naryzhnaya; E. Yu. Varakuta; A. V. Potapov (Бюллетень сибирской медицины)
Aim. To study the effect of a high-fat, high-carbohydrate diet on retinal morphology of young and old rats in the experiment.Materials and methods. The study was carried out on male Wistar rats aged 60 and 450 days at the beginning of the experiment. The animals were divided into 4 groups: group 1 (n = 14) included intact rats aged 150 days at the end of the experiment; group 2 (n = 14) encompassed rats (60 days old) fed with a high-fat, high-carbohydrate diet (HFHCD) for 90 days; group 3 (n = 14) included intact rats (450 days old) receiving a standard diet for 90 days; group 4 (n = 14) included rats (450 days old) fed with HFHCD for 90 days. Immunoassay and histology were used in the work.Results. HFHCD resulted in an increase in glucose concentration in animals of both age groups. In old animals, it caused a pronounced increase in the content of insulin, TGFβ, and fibronectin in the blood serum, neovascularization of outer retinal layers, as well as karyopyknosis and death of neurosensory cells, leading to destruction of photoreceptors and drastic thinning of the outer nuclear and outer plexiform layers. In young rats fed with HFHCD, no pronounced histologic disorders of the retina were noted.Conclusion. HFHCD enhances age-related retinal changes in old (450-day-old) rats.